Sinergi Motivasi dan Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan Pada PT. Paraduta Servis Indonesia - Indriyani, Nesti; Nuraeni, Nuraeni (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to test and analyze the influence of work motivation and work discipline on employee performance. The data collection method in this study was carried out by distributing questionnaires to 45 employee respondents of PT. Paraduta Sevis Indonesia. The research method used is a quantitative method that is associative using primary data. The results of this study indicate that work motivation has a positive and significant effect on employee performance with a t value of 3.286> 2.018 and a significant 0.000 <0.050, work discipline has a positive and significant effect on employee performance with a t value of 2.736> 2.018 and a significant 0.000 <0.050.